Treatment of Municipal Wastewater Using Electrocoagulation Process - Hanumanthaiah, Abhishek; Hanumanthanaik, Vijayakumar; Chitrahalli Lingaraju, Mahesh Kumar; Kotagi Girisha, Shwetha (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Treatment of Municipal wastewater by Electrocoagulation (EC) process using punched aluminium and zinc electrodes was studied in a batch EC cell reactor. Response surface methodology (RSM) based on Central Composite Design (CCD) was utilized to optimize the operating parameters for the removal of % Total Suspended Solids (TSS) and % Chemical Oxygen Demand (COD) from Municipal Sewage. Effect of operating parameters such as Electrode Distance (x1), Electrolysis Time (x2) and Voltage (x3) has been optimized for the removal of TSS and COD.
Keywords: electrocoagulation (EC); municipal sewage; central composite design (CCD); response surface methodology (RSM); total suspended solids (TSS)